2011
DOI: 10.1074/jbc.m111.225052
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Dynamics, Lipid Binding, and Physiological Relevance of the Putative GTPase-binding Domain of Dictyostelium Formin C

Abstract: Dictyostelium Formin C (ForC) is involved in the regulation of local actin cytoskeleton reorganization (e.g. during cellular adhesion or migration). ForC contains formin homology 2 and 3 (FH2 and -3) domains and an N-terminal putative GTPase-binding domain (GBD) but lacks a canonical FH1 region. To better understand the role of the GBD, its structure, dynamics, lipid-binding properties, and cellular functions were analyzed by NMR and CD spectroscopy and by in vivo fluorescence microscopy. Moreover, the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…In the absence of micelles, the presence of the FATC domain in a mostly unstructured, flexible form may further result in an additional viscous drag. A similar effect has been observed for the N-terminal domain of formin C, which contains a large unstructured loop (56). The 15 N T 1 and T 2 and { 1 H}-15 N NOE data for only the FATC part of the free and micelle-immersed fusion protein are shown in Fig.…”
Section: A Comparison Of the 15 N Relaxation Data Of The Free And Micsupporting
confidence: 51%
“…In the absence of micelles, the presence of the FATC domain in a mostly unstructured, flexible form may further result in an additional viscous drag. A similar effect has been observed for the N-terminal domain of formin C, which contains a large unstructured loop (56). The 15 N T 1 and T 2 and { 1 H}-15 N NOE data for only the FATC part of the free and micelle-immersed fusion protein are shown in Fig.…”
Section: A Comparison Of the 15 N Relaxation Data Of The Free And Micsupporting
confidence: 51%
“…Of note, the tertiary structure of the ForC-GBD was shown to adapt an ubiquitin-like fold (66), which is, when combined with positively charged patches at the interaction surface, a hallmark of RBDs (45). In higher eukaryotes, the closest homologs of ForG are members of the FHOD family (28), which are actin-bundling proteins mainly found in stress fibers (67).…”
Section: Resultsmentioning
confidence: 99%
“…To mimic the restriction of mobility in the full-length protein, the 26-mer peptide could further be circularized by oxidation of terminal cysteines. Whereas the full N-terminal domain and the mutant form lacking the loop showed strong spectral changes in the presence of pure DPC micelles and even more if containing negatively charged lipids, neither the reduced nor the oxidized 26-mer peptide showed any spectral changes in CD or NMR spectra upon addition of 50 mM DPC [49]. In contrast to the y1fatc protein analyzed in this study, the Formin C N-terminal domain showed only very minor spectral changes with bicelles, presumably because its interaction with membrane mimetics may be more sensitive to the packing and accessibility of the hydrophobic acyl chains and not only to the curvature [49].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the full N-terminal domain and the mutant form lacking the loop showed strong spectral changes in the presence of pure DPC micelles and even more if containing negatively charged lipids, neither the reduced nor the oxidized 26-mer peptide showed any spectral changes in CD or NMR spectra upon addition of 50 mM DPC [49]. In contrast to the y1fatc protein analyzed in this study, the Formin C N-terminal domain showed only very minor spectral changes with bicelles, presumably because its interaction with membrane mimetics may be more sensitive to the packing and accessibility of the hydrophobic acyl chains and not only to the curvature [49]. Another example for a protein region that shows no interactions with DPC micelles is the N-terminal natively unstructured region of the mycobacterial kinase G (PknG, residues 1-76, Uniprot ID P65728) (unpublished data).…”
Section: Discussionmentioning
confidence: 99%